Waste Is the New Wealth – Recovering Resources From Poultry Wastewater for Multifunctional Microalgae Feedstock - Thoré, Eli S. J.; Schoeters, Floris; De Cuyper, Audrey; Vleugels, Rut; Noyens, Isabelle; Bleyen, Peter; Van Miert, Sabine (Frontiers in Environmental Science, 2021)
To meet the increasing demands of the growing population and to cope with the challenges of global change, both the production of biological feedstock and the recovery of recyclable natural resources play a critical role. Microalgal biomass is a promising source of renewable multifunctional feedstock, but the production is costly and requires large amounts of water. Here, we explored the potential of using wastewater as culture medium to lower the economic and environmental costs of microalgae biomass production and evaluated its valorization opportunities for animal feed production. As a proof of principle, we show that Chlorella sorokiniana can be cultivated on poultry wastewater, with a 83% and 113% increase in productivity when wastewater was first 50% diluted with tap water or standard growth medium, respectively. Wastewater sterilization before use enhanced algal growth with 36-118%, but only when wastewater was 25-50% diluted with standard medium. In contrast, it offered no additional benefits when dilutions were made with tap water or when wastewater was not diluted. At the end of the 22-days experiment, a maximum biomass of 0.8-1.9 g L-1 was reached for algae grown on wastewater. The produced biomass had a high macronutrient content, and the heavy metal content was below maximum limits for use in animal feed. Likewise, the tested pathogen groups were reduced until below safety norms for feed production after algal growth in unsterilized 50% wastewater (diluted with tap water). Overall, these findings add to our growing knowledge on the cultivation of microalgae on wastewater and its valorization opportunities, paving the way for a more sustainable use and reuse of resources.